Pengaruh Persepsi Kemudahan dan Persepsi Manfaat Terhadap Minat Penggunaan E-Payment QRIS (Studi Kasus Pada Pengguna E-Payment QRIS Bank BCA di Kota Bekasi Timur) - Rousdy Safari Tamba; Vina Sawalti (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract.This study aims to determine how much influence the perception of convenience and perception ofbenefits have on the interest in using Bank BCA QRIS E-Payment IN East Bekasi City. This studyuses a quantitative method approach. Data collection techniques were used in the form ofquestionnaires and literature. The sample in this study were people who had used the QRIS BankBCA service as a payment method in transactions, especially respondents who live in East BekasiCity with a sample size of 110 people. The sampling technique used was the Purposive Sampling. The results of the data analysis of this study used the coefficient of determination of the R Square value which showed that the perception of convenience (X1) and the perception of benefits (X2)had a joint contribution of 74,9% to the interest in use (Y), while the remaining 25.1% wasinfluenced by othe factors outside this study. Thus, thw perception of convenience and theperception of benefits have a dignificant effect on the interest in using QRIS E-Payment od BankBCA in East Bekasi City.Keywords: Perception of Convenience; Perception of Benefits, Interest In Use